Generation of two pairs of induced pluripotent stem cells from Angelman syndrome patients with class I 15q11.2-q13.1 deletions and their unaffected familial controls - João Camões dos Santos; Francisca Cazaux Mateus; Maria Arez; Evguenia P. Bekman; Simão T. da Rocha (Stem Cell Research)
Angelman syndrome (AS) is a rare neurodevelopmental disorder characterized by severe developmental delay, speech impairment, ataxia and happy demeanor. AS is caused by loss-of-function of maternal UBE3A in neurons due to (epi)genetic abnormalities. Here, we report two new induced pluripotent stem cell (iPSC) lines from male and female patients carrying ∼ 6 Mb deletions in chr15q11.2-q13.1, together with familial control iPSC lines. All lines express pluripotent stem cell markers, demonstrate trilineage differentiation, and maintain genetic and epigenetic integrity at the locus of interest. These iPSCs provide a platform to model class I deletions, the most severe AS cause, and accelerate therapy development.